Patient safety culture in Slovenian out-of-hours primary care clinics - Klemenc-Ketiš, Zalika (Zdravstveno varstvo, 2017)
Introduction. Patient safety culture is a concept which describes how leader and staff interaction, attitudes, routines and practices protect patients from adverse events in healthcare. We aimed to investigate patient safety culture in Slovenian out-of-hours health care (OOHC) clinics, and determine the possible factors that might be associated with it. Methods. This was a cross-sectional study, which took place in Slovenian OOHC, as part of the international study entitled Patient Safety Culture in European Out-of-Hours Services (SAFE-EUR-OOH). All the OOHC clinics in Slovenia (N=60) were invited to participate, and 37 agreed to do so; 438 employees from these clinics were invited to participate. We used the Slovenian version of the Safety Attitudes Questionnaire % an ambulatory version (SAQAV) to measure the climate of safety. Results. Out of 438 invited participants, 250 answered the questionnaire (57.1% response rate). The mean overall score % standard deviation of the SAQ was 56.6%16.0 points, of Perceptions of Management 53.6%19.6 points, of Job Satisfaction 48.5%18.3 points, of Safety Climate 59.1%22.1 points, of Teamwork Climate 72.7%16.6, and of Communication 51.5%23.4 points. Employees working in the Ravne na Koroškem region, employees with variable work shifts, and those with full-time jobs scored significantly higher on the SAQ-A V. Conclusion. The safety culture in Slovenian OOHC clinics needs improvement. The variations in the safety culture factor scores in Slovenian OOHC clinics point to the need to eliminate variations and improve working conditions in Slovenian OOHC clinics.
Keywords: dežurna služba; kultura varnosti; out-of-hours medical care; primarna zdravstvena raven; primary health care; safety culture; Slovenia; Slovenija